Peran Penalaran Hukum Dalam Penegakan Hukum Tindak Pidana Penyalahgunaan Bahan Bakar Minyak Bersubsidi - Rahman, Habibur; Abadi, Suwarno (Universitas Wijaya Putra, 2025)
Legal reasoning is a logical process essential for determining justice and legal certainty, particularly in criminal cases. This article examines legal reasoning in the context of the misuse of subsidized fuel (BBM), which has become a critical issue in Indonesia. The misuse of subsidized fuel not only causes economic losses to the state but also impedes social justice for communities entitled to such subsidies. Using a normative approach, this article analyzes the application of criminal law to perpetrators of subsidized fuel misuse, referring to existing legislation such as Law Number 22 of 2001 on Oil and Gas. Legal reasoning in this case involves identifying the elements of criminal acts, interpreting legal norms, and applying appropriate criminal sanctions. Furthermore, this article explores the use of deductive, inductive, and analogical reasoning methods in assessing the conformity of perpetrators' actions with applicable legal norms. The analysis results show that proper legal reasoning is necessary to ensure that perpetrators of subsidized fuel misuse are prosecuted fairly and effectively. Consistent law enforcement is also expected to create a deterrent effect and promote the efficient distribution of subsidized fuel to communities in need. This article concludes that legal reasoning plays a crucial role in addressing the complexities of subsidized fuel misuse cases while strengthening the legal system to protect the interests of the state and society.